Contextual intervention adapted for Autism Spectrum Disorder: An RCT of a Parenting Program with Parents of Children Diagnosed with ASD - pashazadehazari, mina; Hosseini, Seyed Ali; Rassafiani, Mehdi; Samadi, Sayyed Ali; Hoseinzadeh, Mehdi; Dunn, Winnie (Iranian Journal of Child Neurology, 2019)
ABSTRACT Background: This study investigated the effects of a manualized Contextual Intervention adapted for Autism Spectrum Disorders (CI-ASD), and essential elements of the intervention in promoting children’s participation and mothers’ parenting self-efficacy. Methods: Researchers conducted a randomized controlled trial. Participants (36 parents of children with ASD) were randomly assigned to wait-list control or intervention groups. The intervention comprised contextually reﬂective occupational therapy combines 3 elements: sensory processing patterns, coaching, and social support. We provided the program to promote child’s participation and parent’s efficiency. During phases 1 the participants in the intervention group received CI-ASD as long as Treatment As Usual (TAU) and during phase 2 they received TAU only. We completed the outcome measures at three time points (pre-intervention, post-intervention and follow-up). Researchers conducted semi-structured interviews post-intervention to explore acceptability of intervention and participants’ experiences of CI-ASD. Results: The findings of the study indicate that CI-ASD can produce meaningful effects in eliminating sensory issues, promoting child participation and parenting efficiency in ASD families, compared to TAU. Parents reported high levels of acceptance and also confirmed the family’s achievements. Conclusion: These gains suggest CI-ASD as an effective intervention for children who have ASD and their families, but further studies are needed to declare and generalize the findings over time. Estimated effect sizes were in the large and medium ranges and favored the intervention group.